PERLINDUNGAN DAN PENEGAKAN HUKUM TERHADAP KASUS KEKERASAN SEKSUAL PADA ANAK - Trini Handayani (Jurnal Hukum Mimbar Justitia, 2016)
Few times ago, the Indonesian people shocked by sexual abuse case that occurred in educational institutions which was incidentally very trusted institution in building the children’s characters and the parental expectations for their children's academic future. Cases that occurred outside the educational institution also very surprising, it was claimed more than 100 (one hundred) children were sodomized by a person who has well known by the victims. By promising cheap prize and by giving treatment so that they would not report as the victims of sexual violence to anyone. Victims and families delay in reporting to the police because they thought that sexual violence is considered a family disgrace, so there are a lot of victims.Keywords: Sexual Abuse, Victim, Child, and Family Disgrace.